A novel teaching model using a massive online open course for soft skills development in the veterinary medicine curriculum - Pato, Nélida Fernández; Ruíz-Rosillo, María Auxiliadora; Bueno, Lydia Calleja; Hurtado, Isabel Rodríguez; Vivas Urias, María Dolores (Frontiers in Veterinary Science, 2025)
IntroductionTeaching and learning methods in Higher Education are constantly adapting looking for a better achievement of one day competencies in each subject along the Veterinary Medicine Degree. Alfonso X el Sabio University is developing its innovative and pedagogical model, entirely centered on the students and based on the development of the most demanded soft skills by employers named “UAX Skill School.” This model has been created by using Coursera platform and selecting online massive open courses (MOOCS) for being adapted to different subjects to ensure the students develop the most useful soft skills. This research summarizes the process and results of the adaptation and implementation of the MOOC “Learning How to Learn” from the Coursera platform in Parasitic Diseases subject which complements and enhances the learning process of Veterinary students.MethodsDuring 2022–2023, 2023–2024, and 2024–2025 academic years, the MOOC “Learning How to Learn” has been integrated and adapted in the subject of Parasitic Diseases in 7 practical sessions before students performed the MOOC and achieved certification. Medallia survey data has been conducted to review student insights.ResultsStudent participation has been over 90%, the dropout rate is less than 2.8% and the performance and learning experience per academic year have reached. Likewise, the invested time (6.41, 5.09, and 4.19 h respectively) and the global participation 94.16%, as well as the conformity of the students with respect to the learning process with grades from 7.85 before the introduction of the pedagogical model to 8.59 after it.DiscussionInnovative methodologies centered on technology are valuable for developing soft skills as evidenced by the implementation of the MOOC “Learning How to Learn” within the context of Parasitic Diseases. Key success factors include the adaptation and integration of these resources into the curriculum. Further research is required to attain a comprehensive understanding of the potential impact of this MOOC on the learning outcomes and soft skills development of Veterinary students.